EVALUASI KONDISI JARINGAN DRAINASE KECAMATAN JOHAN PAHLAWAN BERDASARKAN PERSEPSI MASYARAKAT - Cut Suciatina Silvia (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2017)
The capacity and functions of the drainage has decreased due to the superficiality in drainage, such as the garbage and soil sedimentation that brought by rain water. The system of drainage networks not interconnected and defective building drainage has due the quality is not worth. This is a problem that often occurs in particular in the area of Gampong Kuta Padang, Meulaboh. Based on these conditions, it need to do research and evaluation with problems of system drainage networks in the area of study. Evaluation of existing drainage/channel condition and how public perception or the Government in doing the management of sustainable drainage systems. Evaluation results indicate there is still a channel that is not integrated with other channels, as a secondary channel that is not integrated with the primary channel, the existence of sedimentation and trash that accumulates in drainage resulting in water flow is obstructed, the drainage is wrecked because the quality of drainage are constructed does not have good quality. The results from assessment of the existing drainage conditions, the role of Government and society participation. In the event of the management of sustainable drainage system with 93 peoples of respondents, shows that participation of society and the role Government still belongs to the low with average of 3.55%. With this condition expected active participation of society and the Government in the future could increase the dissemination importance of maintaining for quality of the building infrastructure and the encouraged participation active of society cance development planning. Key Words: Drainage Function, Problems Of Drainage, The Drainage Network